The Effectiveness of the Global Governance of the EU through EASA in its Grounding Boeing 737 MAX Decision on Member Countries - Probo Darono Yakti (WIMAYA, 2022)
This paper will discuss the effectiveness of the European Union (EU) within the framework of global governance to recommend a grounding policy for Boeing 737 MAX 8 to countries that are members of the European Aviation Safety Agency (EASA). Through the EU's global governance approach, this paper will fully elaborate on the domino effect of the recommendations on member countries. Previously, we will discuss the background, the regional governance currently underway in the EU, the chronology of the incident of the accident of two airlines B737-8 aircraft that are outside of EASA and the EASA response in the form of US product grounding recommendations, and then the state response member countries against EASA recommendations. So, in the end, it can be concluded that EASA gets 50 percent effectiveness because the distance between the event and the recommendations issued is considered too hasty so the joining of member countries with EU attitudes generally does not run simultaneously. The importance of this research is to try to test the effectiveness of regional organizations in administering governance through agencies that stand under it.